Level dan Lama Pemberian Jus Kunyit (Curcuma domestica Val.) terhadap Jumlah Telur Cacing Ascaridia galli dalam Ekskreta Ayam Pedaging : Level and Duration of Administration of Turmeric Juice (Curcuma Domestica Val.) to the Number of Ascaridia galli Worm Eggs in Broiler Excreta - Puspitasari, Yuliani Catur; Herawati, Herawati (Jurnal Riset Agribisnis dan Peternakan, 2024)
The health of broiler chickens is improved by the addition of turmeric. Turmeric improves the health of broiler chickens. The purpose of the study was the effect of turmeric juice in drinking water on the number of Ascaridia galli worm curls in broiler chickens. The treatment of this study was the addition of turmeric juice: Po = 0 g / 500 ml, P1 = 10 g / 500 ml, T2 = 20 g / 500 ml, P3 = 30 g / 500 ml.  The design used is a complete random design factorial pattern i.e. level and duration of turmeric juice administration. The results of anova showed that turmeric juice levels were significantly different from the number of Ascaridia galli worm eggs in broiler chickens.  Average number of eggs Ascaridia galli Po= 27.93±1.36; P1= 9.90±1.68; P2=8.92±1.73; P3=5.25±1.25. The duration of administration of turmeric juice differs markedly from the number of eggs of Ascaridia galli worms in broiler chickens. Average number of eggs Ascaridia galli M2=18, 53±1.6c; M3=13, M4=50±2.15; M5=10, 57±2.69 and M6=9.40±2.90. The level of turmeric juice for broiler chickens affects the number of Ascharidia galli worm eggs in excreta. The duration of administration of turmeric juice levels for broiler chickens affects the number of Ascharidia galli worm eggs in excreta. There was an interaction between turmeric juice levels and the duration of administration of the number of Ascharidia galli worm eggs on excreta. It is recommended that turmeric juice be given to broiler chickens with a level of 10 g / 500 ml, and real results are seen in the 3rd week.